2006
DOI: 10.1309/dtyra91g8r0ktm8m
|View full text |Cite
|
Sign up to set email alerts
|

Altered Expression, Localization, and Phosphorylation of Epithelial Junctional Proteins in Celiac Disease

Abstract: We aimed to study the expression and localization of the molecular components of enterocyte junctions in celiac disease together with the level of tyrosine phosphorylation, a phenomenon known to affect their cellular distribution and function, and to explore the influence of proinflammatory cytokines. Duodenal biopsy specimens from patients with celiac disease and control subjects were used for immunoprecipitation, immunoblotting, and immunolocalization by using antioccludin, anti-zonula occludens (ZO)-1, anti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
34
0
4

Year Published

2010
2010
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 92 publications
(42 citation statements)
references
References 37 publications
4
34
0
4
Order By: Relevance
“…This is in line with a report of Hamada et al , in which a methotrexate-associated rearrangement of ZO-1 was associated with its phosphorylation status 38. These data therefore suggest that diminished tyrosine phosphorylation leads to ZO-1 redistribution with a consequent weakening of the epithelial barrier 8. Studies on ZO-1/-2-deficient epithelial cells have shown that reintroduction of ZO-1 determines the location of TJ assembly with the plasma membrane, thereby highlighting the functional importance of ZO-1 association with distinct parts of the cell membrane 39.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…This is in line with a report of Hamada et al , in which a methotrexate-associated rearrangement of ZO-1 was associated with its phosphorylation status 38. These data therefore suggest that diminished tyrosine phosphorylation leads to ZO-1 redistribution with a consequent weakening of the epithelial barrier 8. Studies on ZO-1/-2-deficient epithelial cells have shown that reintroduction of ZO-1 determines the location of TJ assembly with the plasma membrane, thereby highlighting the functional importance of ZO-1 association with distinct parts of the cell membrane 39.…”
Section: Discussionsupporting
confidence: 93%
“…Szakal and coworkers studied the expression level of a subset of TJ proteins—namely, claudin-2, -3 and -4, and showed an increased expression for the pore-forming TJ protein claudin-2 as well as an elevation of the tightening TJ protein claudin-3, thereby leaving the question more or less unresolved, whether there is a contribution of claudins to the CD epithelial barrier defect 9. A study by Ciccocioppo and coworkers evaluated the expression level of another TJ-strand associated protein, ZO-1, which is considered to be of regulatory importance and identified a reduced phosphorylation status of ZO-1 in CD, while the ZO-1 expression level was unaltered 8. Additionally, occludin levels were detected to be lower in CD, which was interpreted as the result of the change in ZO-1 phosphorylation status.…”
Section: Discussionmentioning
confidence: 99%
“…Gluten withdrawal from the diet allowed normalization of the ZO-1 expression in treated celiac disease patients suggesting that the regulatory mechanisms involved are fully reversible. Conversely, a more recent study showed that the molecular rearrangement of TJs and AJs proteins was consecutive to inappropriate levels of tyrosine phosphorylation and no difference in expression of ZO-1, -catenin, occludin and-E-cadherin was found in the duodenum of patients with untreated celiac disease [68]. Drastic reductions of ZO-1 phosphorylation and excessive phosphorylation of -catenin impaired the interaction of these proteins with their natural partners, occludin and E-cadherin, respectively, leading to disruption of AJCs and redistribution of components in cytoplasmic pools.…”
Section: Celiac Diseasementioning
confidence: 93%
“…During early stages of the disease, endocytotic uptake and apical-to-basolateral transcytosis is a common route for gliadin passage 87,88 while deregulation of the paracellular pathway by TJ alterations is more typically associated with advanced stages. [89][90][91] However, the occurrence of increased intestinal permeability in healthy relatives of patients 92 and the discovery of disease susceptibility genes encoding for proteins involved in TJ assembly (MYO9B, PAR-3, MAGI-2) suggest that a primary barrier defect could facilitate the onset and/or perpetuation of the disease. Whether primary defects can contribute to the uptake of gliadin or its cleavage products and trigger disease activation is yet to be diagnosed, as a role for the paracellular pathway in gliadin transport-at least in early stages of the disease-is controversial.…”
Section: Celiac Diseasementioning
confidence: 99%